Avian malaria infections in western European mosquitoes - Ventim, R. (2016)
Avian malaria infections in western European mosquitoes. Ventim R, Ramos JA, Osório H, Lopes RJ, Pérez-Tris J, Mendes L. SourceInstitute of Marine Research (IMAR/CMA), Department of Life Sciences, University of Coimbra, Apartado 3046, 3001-401 Coimbra, Portugal. ritaventim@gmail.com Abstract In the complex life cycle of avian malaria parasites (Plasmodium sp.), we still have a poor understanding on the vector-parasite relationships. This study described the community of potential avian malaria vectors in four Portuguese reedbeds. We tested if their geographical distribution differed, and investigated on their Plasmodium infections. The mosquitoes' feeding preferences were evaluated using CO(2), mice, and birds as baits. The most abundant species were Culex pipiens, Culex theileri, and Ochlerotatus caspius (and, in one site, Coquillettidia richiardii). Plasmodium lineages SGS1 and SYAT05 were found in unengorged Cx. pipiens and Cx. theileri, respectively, suggesting that these mosquitoes were competent vectors of those lineages. The species' abundance was significantly different among sites, which may help to explain the observed differences in the prevalence of SGS1. At the study sites, SGS1 was detected in the most abundant mosquito species and reached a high prevalence in the most abundant passerine species. Probably, this parasite needs abundant hosts in all phases of its cycle to keep a good reservoir of infection in all its stages. Cq. richiardii showed an opportunistic feeding behavior, while Cx. pipiens appeared to be more mammophilic than previously described, perhaps because the used avian bait was not its preferential target. In one of the study sites, mosquitoes seem to be attracted to the Spotless Starling Sturnus unicolor, an abundant bird species that may be an important local reservoir of avian malaria infections. To our knowledge, this is the first report of detection of avian Plasmodium DNA from European mosquitoes.